2011
DOI: 10.4103/0019-509x.92277
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver reproducibility of Gleason grading of prostatic adenocarcinoma among general pathologists

Abstract: In our study interobserver reproducibility of Gleason scores among general pathologists was at lower level and it highlights the need to improve the observer reproducibility by continuous educational sessions and taking second opinion in cases where grade could significantly influence management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
(56 reference statements)
0
19
0
Order By: Relevance
“…However, before moderation of postoperative surveillance is considered for any pGS6 patient, it may be necessary to confirm the absence of Gleason pattern 4 by RP pathology review. Gleason pattern 4 can be frequently identified among even BF‐free pGS6 patients (38% rate in the current study), which underscores inter‐observer variability in pGS6 grade assignment . At RPCI, we discuss the option of deferring radiation with pGS6 patients who develop BF, if independent RP pathology review in a formal multidisciplinary tumor board confirms the absence of a higher Gleason pattern.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, before moderation of postoperative surveillance is considered for any pGS6 patient, it may be necessary to confirm the absence of Gleason pattern 4 by RP pathology review. Gleason pattern 4 can be frequently identified among even BF‐free pGS6 patients (38% rate in the current study), which underscores inter‐observer variability in pGS6 grade assignment . At RPCI, we discuss the option of deferring radiation with pGS6 patients who develop BF, if independent RP pathology review in a formal multidisciplinary tumor board confirms the absence of a higher Gleason pattern.…”
Section: Discussionmentioning
confidence: 66%
“…However, a limitation of these studies is that regrading was performed by a single pathologist who was aware of the metastasis outcomes and study objectives, which introduces potential for upgrading bias. Given the practical subjectivity and inter‐observer variability of Gleason score assignment, these findings require confirmation using an unbiased study design with multiple independent blinded pathologists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our result is better than Coard & Freeman's study, which showed 60% concordance rate . Similarly, Singh et al found low level of reproducibility among general pathologists. Besides, Melia et al reported the intra‐observer agreement among uropathologists to be only 77%.…”
Section: Discussionmentioning
confidence: 98%
“…variability (37)(38)(39). That ploidy measurement by itself cannot make Gleason grading "safe" in its capability to identify the "dangerous" cancers is, however, demonstrated by the 39.9% of Gleason !4þ4 cancers (known to have a dismal prognosis), and the 55.2% of cancers with PSA recurrence, having a diploid DNA content.…”
Section: Discussionmentioning
confidence: 99%